Un-Proportional Municipal Waste Plastic Conversion into Fuel using Activated Carbon and HZSM-5 Catalyst - Moinuddin Sarker; Mohammad Mamunor Rashid; Mohammed Molla ; Md. Sadikur Rahman (Journal of Applied Chemical Science, 2012)
The demand of fuel continues to increase throughout the world. Over 81 million barrels of liquid fuel are consumed everyday worldwide for transportation vehicle; excluding the amount needed to produce plastics for daily use. Most of the transportation fuel is produced from crude oil, and this non renewable resource is declining day by day. With this decline in mind, the politicians and scientific community should emphasize more research to preserve this natural resource. Worldwide researchers are working to find out suitable environment friendly sustainable alternate source of liquid fuel. Now day’s plastic use are increasing constantly because plastics are light weight, durable and easy to use. After the short use, plastics become waste and create lots of problem for the environment. Plastic is not a biodegradable substance, and due this nature it remain in landfill for very long time; polluting the environment and its inhabitants. An established method has been studied and successfully demonstrates which converts majority of the waste plastic into liquid hydrocarbon fuel and can be used to power internal combustion engines. This new conversion process is an environment friendly and cost effective process that helps to preserve the environment while protecting our valuable natural resources.